2015
DOI: 10.1017/s1368980015002992
|View full text |Cite
|
Sign up to set email alerts
|

Reducing discretionary food and beverage intake in early childhood: a systematic review within an ecological framework

Abstract: Objective: To systematically review the literature and map published studies on 4-8-year-olds' intake of discretionary choices against an ecological framework (ANalysis Grid for Environments Linked to Obesity; ANGELO). Design: Articles were identified through database searches (PubMed, PyscINFO ® , Web of Science) in February and March 2014 and hand-searching reference lists. Studies were assessed for methodological quality and mapped against the ANGELO framework by environment size (macro and micro setting) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Homes are a natural setting for nutrition promotion with 60-70% of children's food intake provided from within this setting [7,8] (Price 2014, unpublished findings). Parents are the primary "gatekeepers" within homes, serving as role models, determining food availability and setting the family norms that shape children's habits [9]. Nutrition promotion interventions where parents are the primary change agent are effective [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Homes are a natural setting for nutrition promotion with 60-70% of children's food intake provided from within this setting [7,8] (Price 2014, unpublished findings). Parents are the primary "gatekeepers" within homes, serving as role models, determining food availability and setting the family norms that shape children's habits [9]. Nutrition promotion interventions where parents are the primary change agent are effective [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…
25Objective 26 To explore dietary differences according to socioeconomic and sociocultural characteristics of 27 adolescents and young adults. 28 Design 29 A systematic review was conducted.
…”
mentioning
confidence: 99%
“…As any form of added sugar contributes to both dental caries and obesity, there is a need to review education and social policies about foods and SSBs that are marketed to children. Parents have identified that the marketing of SSBs is a key factor influencing child drink choice and consumption (Hennessy, Bleakley, Piotrowski, Mallya, & Jordan, 2015; Johnson, Hendrie, & Golley, 2016).…”
Section: Discussionmentioning
confidence: 99%